A Study of Impulsive Multiterm Fractional Differential Equations with Single and Multiple Base Points and Applications. (21st January 2014) - Liu, Yuji; Ahmad, Bashir
Abstract : We discuss the existence and uniqueness of solutions for initial value problems of nonlinear singular multiterm impulsive Caputo type fractional differential equations on the half line. Our study includes the cases for a single base point fractional differential equation as well as multiple base points fractional differential equation. The asymptotic behavior of solutions for the problems is also investigated. We demonstrate the utility of our work by applying the main results to fractional-order logistic models.